2016
DOI: 10.1097/ncc.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Symptom Cluster Subgroups Among Men Undergoing Prostate Cancer Radiation Therapy

Abstract: Background Prostate cancer is a common type of cancer worldwide and in the United States. However, little information has been reported on the symptoms of men overtime who receive radiation therapy. Objective Identify subgroups of men at pre-and post radiation therapy on general and treatment-related symptoms and to determine transitions in subgroup membership overtime. Methods Men (n=84) receiving completed questionnaires on fatigue, insomnia, pain, depression, anxiety, and sexual, urinary and bowel probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Our findings are consistent with previous studies that applied similar methods for subgroup analyses of HRQOL in patients with cancer. One study of 84 men with prostate cancer who received radiation therapy also identified 4 HRQOL subgroups or profiles . From best to poorest HRQOL 8 weeks after starting therapy, the profiles were labeled as “resilient,” “adjusted,” “emerging,” and “distressed.” Similar to our study, younger men were more likely to be in the distressed profile.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous studies that applied similar methods for subgroup analyses of HRQOL in patients with cancer. One study of 84 men with prostate cancer who received radiation therapy also identified 4 HRQOL subgroups or profiles . From best to poorest HRQOL 8 weeks after starting therapy, the profiles were labeled as “resilient,” “adjusted,” “emerging,” and “distressed.” Similar to our study, younger men were more likely to be in the distressed profile.…”
Section: Discussionmentioning
confidence: 99%
“…A few cross-sectional studies ( 13 15 ) classified patients into subgroups using LCA, but a limited number of studies used longitudinal data. Four studies explored subgroups of patients prior and after chemotherapy based on symptom occurrence or severity in a heterogeneous sample ( 16 , 17 ) or specific cancer type of patients ( 18 , 19 ). Different distinct subgroups, transition status, and patient characteristics were identified using LCA and LTA.…”
Section: Introductionmentioning
confidence: 99%
“…Income and economic status were also implicated in psychoneurological symptom clusters, with five studies ( n = 4 cancer and n = 1 COPD) finding significant relationships between lower income or self‐reported poor economic status and higher levels of symptoms such as pain, fatigue, and depression (Chu et al, 2019; Dirksen et al, 2016; Ji et al, 2017; Langford et al, 2016; Lim et al, 2017). Again, specific symptoms included in the psychoneurological symptom cluster differed across studies, with one study including posttraumatic stress type symptoms (e.g., re‐experiencing; Chu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Among the most analyzed Social and Community Context variables were age (n =44, 37.29%), sex/gender (n =24, 20.33%), and race/ ethnicity (n =18, 18.64%). Regarding age, 16 studies in oncology populations found a significant association between age and symptom clusters (Baden et al, 2020;Bjerkeset et al, 2020;Bobevski et al, 2018;Dirksen et al, 2016;Fox et al, 2020;Gehrman et al, 2017;Jeon et al, 2019;Lee et al, 2020;Lemanska et al, 2017;Levkovich et al, 2018;H. Li et al, 2020;Nho et al, 2017;Papachristou et al, 2018;Ren et al, 2017;Seib et al, 2017;Wang et al, 2019).…”
Section: Social and Community Contextmentioning
confidence: 99%